Immunogenicity and protective efficacy of recombinant chimeric antigens based on surface proteins of Toxoplasma gondii - Chyb, Maciej; Ferra, Bartłomiej Tomasz; Kawka, Malwina; Skwarecka, Marta; Dziadek, Bożena; Gatkowska, Justyna (Frontiers in Immunology, 2024)
IntroductionToxoplasmosis is caused by the opportunistic, cosmopolitan protozoan Toxoplasma gondii is one of the most common parasitoses in the world. This parasite can pose a threat to people with immunodeficiency but also to the fetus, since the invasion can lead to miscarriages. Moreover, this parasite can contribute to economic losses in livestock farming. These problems lead to the implementation of new, safe solutions for the development of effective toxoplasmosis immunoprophylaxis.MethodsIn this work, newly produced recombinant trivalent chimeric proteins of T. gondii, based on SAG1-SAG2 recombinant chimeric antigen that differ in one terminal antigenic component, were tested in terms of their ability to induce an effective post-vaccination response. Antigens were tested in vitro to assess their ability to elicit APC cells response and further mice of the C3H/HeOuJ strain were immunized using those antigens, to evaluate their immunogenicity and immunoprotective effect in vivo. Two weeks after the last dose mice were either sacrificed to assess selected parameters of the immune response or infected with T. gondii DX strain to determine the degree of protection one month later.ResultsThe results of serological tests revealed a high level of serum IgG antibodies specific for the native T. gondii TLA antigens. TLA-stimulated splenocytes produced cytokines that are important in inhibiting protozoal invasion. Additionally, CD3+ CD4+ and CD3+ CD8+ T cell subpopulations of splenocytes were analysed by flow cytometry. One month after experimental infection mice were sacrificed, and their brains were isolated to count T. gondii tissue cyst. Immunization of mice with recombinant trivalent chimeric proteins of T. gondii resulted in reduction of tissue cyst burden rates reaching even 74%.DiscussionThe obtained results demonstrate strong immunogenicity of the studied proteins and will allow to select candidates for further research aimed at increasing the immunoprotective properties of experimental vaccines against toxoplasmosis based on T. gondii chimeric antigens.